Foot Hydrotherapy Using Pandan Leaves (Pandanus amaryllifolius) and Its Effect on Insomnia in Adolescents - Ni Made Larasati; Ni Rai Sintya Agustini; Yohanes Zenriano Tarigan (Pubfine Media Group, 2026)
Introduction: Insomnia is a sleep disorder characterized by difficulty in initiating or maintaining sleep despite having the opportunity to rest. This condition can lead to disturbances in daytime activities, fatigue, and frequent awakenings during the night. Furthermore, insomnia can have negative effects on health, such as increasing the risk of heart disease, metabolic disorders, cognitive decline, and even mortality. Adolescents are among those at risk of experiencing insomnia, as individuals generally require about 8–10 hours of sleep each night. However, this duration is often reduced due to busy school schedules and social activities, which can trigger sleep disorders such as insomnia. One non-pharmacological approach to overcoming insomnia is foot hydrotherapy using pandan leaves (Pandanus amaryllifolius). The purpose of this study was to determine the effect of pandan leaf foot hydrotherapy on insomnia among adolescents. Methods: This research used a quantitative with a one-group pretest- posttest design. The population consisted of 93 adolescents experiencing insomnia at Jembrana, Indonesia. The sampling technique used in this study was convenience sampling. The instruments used included a demographic data sheet and the Jakarta Insomnia Rating Scale (KSPBJ-IRS) questionnaire. Results: The data analysis was conducted using the Wilcoxon Signed Rank Test, and the results showed a p-value of < 0.001 before and after the intervention. Conclusion: The conclusion of this study is that foot hydrotherapy using pandan leaves (Pandanus amaryllifolius) has an effect on reducing insomnia in adolescents.